Cystatin C Is a Crucial Endogenous Protective Determinant Against Stroke. Issue 2 (February 2017) - Fang, Zongping; Deng, Jiao; Wu, Zhixin; Dong, Beibei; Wang, Shiquan; Chen, Xiaodan; Nie, Huang; Dong, Hailong; Xiong, Lize
Abstract : Background and Purpose—: Endogenous neuroprotection can be induced by ischemic and nonischemic preconditioning. However, not all subjects that undergo preconditioning exhibit similar favorable outcome. This study is to explore the molecules responsible for this phenomenon and find new therapeutic targets for stroke. Methods—: Adult male Sprague–Dawley rats were subjected to transient middle cerebral artery occlusion. High-throughput proteomic technique, isobaric tag for relative and absolute quantification, was used to screen differentially expressed proteins in the rats that developed ischemic tolerance from hyperbaric oxygen (HBO) preconditioning. The proteomic results were verified by Western blot and ELISA. Then, short interfering RNA and gene knockout rats were used to further determine the pivotal role of candidate proteins in HBO preconditioning–induced endogenous neuroprotection. Finally, lysosomal permeability was tested to elaborate the mechanism underlying this intrinsic neuroprotective effect. Results—: Nine proteins differentially expressed in the serum of rats, which acquired benefits from HBO preconditioning, were screened and identified. Western blot and ELISA revealed that cystatin C (CysC) and mannose-binding lectin protein C were uniquely changed in rats with smaller infarction after HBO preconditioning and cerebral ischemia. Knockdown and knockout of CysC abolished HBO-induced neuroprotection. Moreover, HBO-induced endogenous CysC elevation preserved lysosomal membrane integrity after stroke in wild-type rats but not in CysC siRNA infusion or CysC − /− rats. Most importantly, exogenous CysC also induced neuroprotection against ischemic/reperfusion injury. Conclusions—: CysC is a crucial determinant contributing to endogenous neuroprotection. It is also a novel candidate for stroke treatment through maintaining lysosomal membrane integrity. Abstract : Supplemental Digital Content is available in the text.